Using proteolysis-targeting chimera technology to reduce navitoclax platelet toxicity and improve its senolytic activity - Yonghan He (Nature Portfolio, 2020)
Senolytics have the potential to extend healthspan by selectively killing senescent cells (SCs), but senolytics that target Bcl-xl may cause platelet toxicity. Here, the authors generated a Bcl-xl proteolysis-targeting chimera (PROTAC) senolytic, which effectively clears SCs and rejuvenates tissue stem and progenitor cells in naturally aged mice without causing severe thrombocytopenia.